(untitled) (Journal of Guidance and Counselling Studies, 2024)
The paper explores the use of educational psychology in enhancing technology-driven curriculum reforms in Nigerian secondary schools. Educational psychology is pivotal in addressing the psychological, cognitive, and social challenges associated with curriculum reforms by offering insights into how students learn and adapt to new technological tools, and also contribute to the design and implementation of inclusive and adaptable curricula. Educational psychology helps teachers and school administrators in integrating technology, ensuring the mental and emotional readiness of both educators and students for effective teaching and learning. The challenges that affect successful technology-driven curriculum reform in secondary schools; such as limited access to resources and lack of teacher preparedness, and solutions or strategies for overcoming the challenges. The use of educational psychology in technology-integrated curriculum reform, such as promoting inclusivity, facilitating teacher training, addressing technology-induced anxiety, promoting digital literacy, monitoring and evaluation, cognitive considerations in technology integration, learning disabilities and technology, assessment of learning outcomes, curriculum design and development, addressing cognitive and psychological barriers, teacher preparedness and professional development, supporting student adaptation to technological reforms, inclusive education and technology integration among others. Recommendations are as follows; the Nigerian government in collaboration with secondary schools authority should prioritize ongoing professional development programs for teachers and curriculum planners, Schools should establish interdisciplinary teams that include educational psychology, teachers, administrators, and technology experts. Teacher training programs should incorporate psychological readiness where educational psychologists guide teachers in understanding the mental and emotional challenges associated with technology integration.